Perpetual prison in Colombia. Analysis of the Legislative Initiatives for their authorization, and the rational arguments for their incorporation in the Colombian legal system (2019)
In Colombia, around sixteen draft legislative act have been submitted to modify article 34 of the Constitution, thus eliminating the prohibition of life sentences; the most recent has been the project of Legislative Act 001 of 2019, whose content enshrined that the penalty, would only be reviewable, after thirty years of effective deprivation of liberty. The publication aims to trace the attempts made by the legislator so far to incorporate this sanction, and review the arguments used to justify it. The aim is to demonstrate the precarious rationality incorporated in the motives expositions, the legislative debates in committee and in the plenary, the lacking empirical sustention, its weak justification, and the use in its replacement, of an already common punitive populism, with which it contravenes besides the Constitution, the Rules of the Congress and the pronouncements of the Constitutional Court on reflective legislation.